KONSEP KALEPASAN PADA TEKS BUBHUKSAH GAGAKAKING: Perspektif Teologi Hindu - Santika, Ni Made Mitia; D.E., Relin; Pradnya, I Made Adi Surya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
In order to achieve the final goal of this life, namely Moksa, there are various paths that can be taken. Several teaching sources contained in the Vedas, Itihasa, Puranas and Hindu literature are tools to be guided by in order to find the path to kalepasan. One of the sources from Hindu literature that is used as research regarding kalepasan in this case is the Bubhuksah Gagakaking Text. Meanwhile, the methods used are identification of the type of research, intertext observation, documentary, online data search, instruments followed by data analysis techniques and presentation of data analysis results. The text structure consists of Synopsis, Characters, Incidents, Plot, Setting, Theme and Message. Meanwhile, the teachings contained in Bubhuksah Gagakaking's text are Harmony, Moral Teachings, Shiva Buddha Teachings, Peditativity Teachings. The concept of kalepasan that can be explained consists of the Shiva Abhrawi Concept implemented by Gagakaking, namely a path to kalepasan through self-discipline, meditation by becoming a Pandita who always adheres to the provisions of the Veda, is faithful to the promise to avoid various taboos, is always compassionate, and does not commit murder. and abstain from eating meat. Meanwhile, Bubhuksah's concept of kalepasan Buddha Bhrawi is to always be self-disciplined by becoming an ascetic as a Buddhist priest, worshiping diligently facing west, eating everything he likes, killing game animals and eating them without any leftovers, as the basis for liberation of these animals. Kalepasan can be done perfectly through Tyaga Pati, namely self-discipline to follow the path of truth towards God with full sincerity without blaming others. Towards the One God who is supernatural or Acintya as the source of all that exists can be reached with concentration of mind, not through japa, meditation or science.